Analytical and diagnostic performance of an automated anti-CCP assay - Pavai, S.; Sargunan, S.; Zain, A.A.; Chow, S.K. (2011)
AIM: Autoantibodies against cyclic citrullinated peptide (anti-CCP) are considered to be a sensitive and specific marker for rheumatoid arthritis (RA). This study evaluated the diagnostic and analytical performances of the automated anti-CCP assay. MATERIALS AND METHOD: Sera from 80 patients with established RA, 65 from other rheumatic diseases (non-RA) and 55 from healthy controls were studied using second generation anti-CCP. Rheumatoid factor (RF) was also assayed in each sample, and the results were compared to the anti-CCP findings. Serum pools were used to determine the precision and linearity. RESULTS: At a cut-off of 7.4 U/ml for anti-CCP, the sensitivity and specificity for RA were 65% and 98% respectively. RF had a sensitivity of 58% and a lower specificity of 93% than anti-CCP. CONCLUSION: The high specificity of the assay suggests that anti-CCP is useful in the diagnosis of rheumatoid arthritis and in our cohort of study population anti-CCP exhibits a better diagnostic value than RF. A considerable proportion (28%) of RF-negative RA patients were anti-CCP positive. Based on analytical performance of the assay, we conclude that full automation and high throughput features of AxSYM makes it an ideal platform for routine testing of anti-CCP.